Cranial Diabetes Insipidus in Neuropsychiatric Systemic Lupus Erythematosus, a Rare but Treatable Association: A Case Report - Alvin Oliver Payus; Malehah Mohd Noh; Constance Liew Sat Lin; Justin Leow Wen Hsian; Ani Darwina Abdul Halim (2020)
Systemic lupus erythematosus has been rarely reported to be associated with cranial diabetes insipidus. It is a condition clinically manifest as severe polyuria and reactive polydipsia that may lead to electrolyte imbalance or acute kidney injury as a result of arginine vasopressin insufficiency. Here, we report a patient with systemic lupus erythematosus and lupus nephritis previously under control with medication presented with neuropsychiatric symptoms which responded to pulsed methylprednisolone, developed severe polyuria, polydipsia and hypernatremia which persisted after pulsed therapy. Serum and urine osmolarity were suggestive of diabetes insipidus and the polyuria resolved dramatically after trial of oral desmopressin which in keeping with the diagnosis of central cause. The objective of this case report is to share the uncommon occurrence of diabetes insipidus in neuropsychiatric systemic lupus erythematosus.